OPTIMIZATION OF OLIVE OIL, TWEEN 80, AND PROPYLENE GLYCOL OF SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM OF ZINC OXIDE BY D-OPTIMAL METHOD - Dian Eka Ermawati; Adi Yugatama; Wening Wulandari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2020)
The incidence of skin cancer in Indonesia reaches 6-8%, so the skin needs effective protection. Zinc Oxide (ZnO) is a sunscreen with Sun Protecting Factor (SPF) 50 which is able to reduce exposure to Ultraviolet rays. ZnO is difficult to dissolve in water making an obstacle if dispersed in a hydro gel matrix, so it is formulated into a Self-Nanoemulsifying Drug Delivery System (SNEDDS) preparation. SNEDDS formula was made using tween 80 as surfactant, propylene glycol as a co-surfactant, and olive oil. The optimum proportion of the three components was optimized with the D-Optimal method using Design Expert Stat-Ease 9 Trial software. Software obtained 16 formulas which were tested for physical stability response: transmittance value (%) and pH value. SNEDDS optimum formula was compared with the D-Optimal prediction formula using the student's t-test statistical analysis (p0.05), the loading dose of ZnO, Particle Size Analysis, and Zeta Potential. The optimum proportion of propylene glycol, tween 80, and olive oil making up SNEDDS were 9.9%: 81%: 9.1% respectively. The result of the percent transmittance response was 92.30% and the pH value was 7.20. Software prediction results: transmittance value was 92.59% and pH value was 7.37. Statistical analysis of one sample t-test showed no difference between observations and D-Optimal predictions. SNEDDS was able to load 2.0 mg ZnO/gram SNEDDS with a particle size of 150.2 nm; polydispersity index of 0.54 and zeta potential of -28.50 mV. The SPF value of SNEDDS ZnO was 16.